IDNLearn.com offers expert insights and community wisdom to answer your queries. Ask your questions and receive prompt, detailed answers from our experienced and knowledgeable community members.

Select the correct answer.

Solve the following equation for [tex]x[/tex]:
[tex]\[ x^2 - 9x + 18 = 0 \][/tex]

A. [tex]x = -3 ; x = 6[/tex]
B. [tex]x = 3 ; x = 6[/tex]
C. [tex]x = -3 ; x = -6[/tex]
D. [tex]x = 3 ; x = -6[/tex]


Sagot :

To solve the quadratic equation [tex]\( x^2 - 9x + 18 = 0 \)[/tex], we'll use the quadratic formula, which is given by:

[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]

For the given equation [tex]\( x^2 - 9x + 18 = 0 \)[/tex], we have:
- [tex]\( a = 1 \)[/tex]
- [tex]\( b = -9 \)[/tex]
- [tex]\( c = 18 \)[/tex]

First, we calculate the discriminant ([tex]\( \Delta \)[/tex]) using the formula [tex]\( \Delta = b^2 - 4ac \)[/tex]:

[tex]\[ \Delta = (-9)^2 - 4 \cdot 1 \cdot 18 \][/tex]
[tex]\[ \Delta = 81 - 72 \][/tex]
[tex]\[ \Delta = 9 \][/tex]

Since the discriminant is positive ([tex]\( \Delta > 0 \)[/tex]), we have two real solutions. We now substitute into the quadratic formula to find the roots of the equation.

The quadratic formula states:

[tex]\[ x = \frac{-(-9) \pm \sqrt{9}}{2 \cdot 1} \][/tex]
[tex]\[ x = \frac{9 \pm 3}{2} \][/tex]

This gives us two solutions:

1. For the positive root:
[tex]\[ x_1 = \frac{9 + 3}{2} \][/tex]
[tex]\[ x_1 = \frac{12}{2} \][/tex]
[tex]\[ x_1 = 6 \][/tex]

2. For the negative root:
[tex]\[ x_2 = \frac{9 - 3}{2} \][/tex]
[tex]\[ x_2 = \frac{6}{2} \][/tex]
[tex]\[ x_2 = 3 \][/tex]

Therefore, the solutions to the quadratic equation [tex]\( x^2 - 9x + 18 = 0 \)[/tex] are: [tex]\( x = 6 \)[/tex] and [tex]\( x = 3 \)[/tex].

The correct answer is:

B. [tex]\( x = 3 ; x = 6 \)[/tex]